(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Alzheimer`s Disease (AD) is a progressive neurogenerative disease. It is characterized by deterioration of memory, language and other cognitive impairments in elder people. Thiazolidinedione (TZD) scaffold, produce activities like Anti- Alzheimer, Antioxidant, Antimicrobial and Antidiabetic properties. In the present study we use a approach by integrating network pharmacology, molecular docking to explore the Thiazolidinedione derivative against Alzheimer Disease. Totally 435 compounds were retrieved from PubChem are subjected to pharmacokinetic, metabolic and toxicity profiles. The compounds which are having good pharmacokinetic and less toxic are selected. Network pharmacology and gene ontology enrichment were performed to identify the top targets involved in Alzheimer Disease. Molecular docking is performed by using MzDOCK with auto dock vina mode. A total 64 compounds were retrieved from that ten compound were finalized and network was constructed using cytohubba in cystoscope. Top seven targets were identified, top two targets namely STAT 3 and TNF, based on the degree centrality were selected. Molecular docking studies reveal that the compound ((5Z)-3-[2-(4-chlorophenyl)-2-oxoethyl]-5-(furan-2- ylmethylidene)-1,3-thiazolidine-2,4-dione) and ((5Z)-5-[[2-(4-methoxyphenyl)-4-pyridinyl] methylidene]-1,3-thiazolidine-2,4-dione) showed good and highest binding energy and interaction profile. In conclusion the revealed that Thiazolidinedione derivatives can be the best option for the treatment of Alzheimer disease.